Ballot Titles and Voter Decision Making on Ballot Questions. (June 2014) - Hastings, Jeff; Cann, Damon
From gay marriage to taxation to environmental issues, many of our nation's most important policy issues are decided by voters through ballot questions. Conventional wisdom holds that information provided on the ballot about the ballot questions heavily influences voters' choices in those elections, but there is little empirical evidence of this. We apply theories of framing to voters' choices on ballot questions and design an experiment to test the hypothesis that ballot title wording influences voters' decisions. Even on a matter that is hotly contested and where the policy is relatively noncomplex and relatively well understood by voters, we find strong framing effects for changes in ballot title wording, though the effects are driven primarily by influencing whether individuals who previously supported the measure abstained from participation.